Study on influence and compensation for soil compactness on volumetric water content measurement. (October 2019) - Tian, H; Gao, C; Gao, Z T; Zhao, Y D
Abstract: Volumetric water content measurements based on soil dielectric properties are affected by soil compaction. Today's commercial products produce substantial measurement error as they do not account for the influence of soil compaction. This paper presents a portable soil volumetric moisture content sensor based on the principle of standing wave rate and simultaneous soil compactness measurement. The coupling relationship between soil compactness and soil volumetric moisture content can be easily observed by converting them into polar coordinates. A modified soil volumetric moisture content model based on the soil compactness is also established to support the operation of the proposed sensor.